Analisis Berpikir Kritis Siswa dalam Pemecahan Masalah Aljabar Ditinjau dari Gaya Belajar Visual - Agustina, Agustina; Huda, Nizlel; Maison, Maison (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2024)
The inability of students to think critically in solving algebraic problems is evident in their tendency to rely on formulas without a profound understanding of basic algebraic concepts. They struggle to analyze problems and devise appropriate strategies before solving them, often sticking to a singular solution approach without critically exploring alternative solutions. Critical thinking has become a crucial skill in 21st-century learning for discerning truths and making informed decisions, assessed through indicators such as Focus, Reason, Inference, Situation, Clarity, and Overview. Teachers need to comprehend students' learning styles and adjust teaching methods accordingly, as categorized by Porter into three types: visual, auditory, and kinesthetic. This study delves into students' critical thinking in algebra problem-solving concerning their learning styles, utilizing a qualitative descriptive approach with purposive sampling. Based on the provided learning style questionnaire, 61.11% of students from XI IPA MAN 2 Kota Jambi exhibit a visual learning style. Subjects with a visual learning style then undergo a critical thinking test in algebra problem-solving. Research findings reveal a deficiency in students' critical thinking abilities, indicating their struggles in critically analyzing mathematical problems thoroughly.